Socio-Psychological Aspects of Anorexia Nervosa - Haringa, Ivan; Janáčková, Laura; Kardis, Kamil; Gažiová, Maria; Vyacheslavovna, Apakina Liudmila (Journal of Education Culture and Society, 2023)
Aim. The main aim of the research is to identify and evaluate the quality of life of patients with an eating disorder – anorexia nervosa. In an analytical and descriptive way, the authors determine the level of various areas of life of patients who suffer from anorexia nervosa. Methods. The subjects of the study were participants suffering from anorexia nervosa. Based on qualitative research through unstructured interviews, the authors carried out causal case individual investigations, which they classified according to anamnesis, diagnostic tools and areas, which they evaluated based on the statements of the participants. Results. The analysis shows that anorexia nervosa affects different areas of life. It is a lifelong problem that has a huge impact on the physical, psychological, and spiritual side of a person. Conclusion. The study deals with the various elements of anorexia nervosa, which ultimately affects a person for life. Through definitions and interpretations of the authors’ research results, we can confirm that it has multi-problematic consequences for the categorised areas of an individual’s life, for the family and the groups in which they live.